The little flower shop - Foster, Lori (Canary Street Press, 2023)
Forty-two, divorced, and responsible for an aging aunt and uncle, florist Emily Lucretia, deciding to put herself out there, starts dating the owner of the local barbecue joint until her meddling small town gets involved in her relationship, with hilarious and unexpected results.